KEPENTINGAN AMERIKA SERIKAT MENGGUGAT INDONESIA DENGAN KASUS IMPORTATION OF HORTICULTURAL PRODUCTS, ANIMALS AND ANIMAL PRODUCTS - Yana Miranti, Putu Linda; Rainy Priadarsini, Ni Wayan; Parameswari, Anak Agung Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
This study aims to explain what is the interests of the United States (US) has in Indonesia regarding the Regulation of the Minister of Agriculture Number 86 of 2013 concerning Recommendations for the Import of Horticultural Products (RIPH), and Regulation of the Minister of Trade Number 16 in 2013. By sued the regulation to the World Trade Organization (WTO). This study uses descriptive qualitative method. The US has its own interests in sued Indonesian regulations. It can be seen from the post US victory in the WTO, which continues to demand Indonesia to impose a fine of 350 million. US agricultural exports in 2016, have increased and remained stable. This study uses a conceptual framework of national interest. This study finds the answer that the interests of US in Indonesia regarding Indonesia regulations of RIPH, animals and animal products are economic interests, ideological interests and world order interests. Keyword: Amerika Serikat, Kepentingan Nasional, Rekomendasi Impor Hortikultura, Hewan dan Produk Hewan,